Loss of N‐WASP drives early progression in an Apc model of intestinal tumourigenesis. Issue 3 (28th May 2018) - Morris, Hayley T; Fort, Loic; Spence, Heather J; Patel, Rachana; Vincent, David F; Park, James H; Snapper, Scott B; Carey, Francis A; Sansom, Owen J; Machesky, Laura M
Abstract: N‐WASP (WASL) is a widely expressed cytoskeletal signalling and scaffold protein also implicated in regulation of Wnt signalling and homeostatic maintenance of skin epithelial architecture. N‐WASP mediates invasion of cancer cells in vitro and its depletion reduces invasion and metastatic dissemination of breast cancer. Given this role in cancer invasion and universal expression in the gastrointestinal tract, we explored a role for N‐WASP in the initiation and progression of colorectal cancer. While deletion of N‐wasp is not detectably harmful in the murine intestinal tract, numbers of Paneth cells increased, indicating potential changes in the stem cell niche, and migration up the crypt–villus axis was enhanced. Loss of N‐wasp promoted adenoma formation in an adenomatous polyposis coli ( Apc ) deletion model of intestinal tumourigenesis. Thus, we establish a tumour suppressive role of N‐WASP in early intestinal carcinogenesis despite its later pro‐invasive role in other cancers. Our study highlights that while the actin cytoskeletal machinery promotes invasion of cancer cells, it also maintains normal epithelial tissue function and thus may have tumour suppressive roles in pre‐neoplastic tissues. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.